Solid-phase synthesis of 4,7,8-trisubstituted 1,2,3,4-tetrahydro-benzo[e][1,4]diazepin-5-ones - Lemrová, Barbora; Soural, Miroslav (ACS combinatorial science, 2012)
Solid-phase synthesis of 1,2,3,4-tetrahydro-benzo[e][1,4]diazepin-5-ones with use of polystyrene resin is described. The starting material was polymer supported 1,2-diaminoethane and as a key synthon, 4-chloro-2-fluoro-5-nitrobenzoic acid was used. The synthetic approach allows the preparation of derivatives with variable substitution at positions 4 and 8. Additionally, a skeletal diversity was increased when the nitro group was reduced and some benzene fused heterocycles were prepared. An expansion of a diazepinone to a benzodiazocinone scaffold was also successful although some limitations in a diversity of target derivatives were observed.
Keywords: molekulární struktura; benzodiazepiny; Benzodiazepines; Molecular Structure